2022
DOI: 10.3390/cancers14123024
|View full text |Cite
|
Sign up to set email alerts
|

Severe Radiation-Induced Lymphopenia Affects the Outcomes of Esophageal Cancer: A Comprehensive Systematic Review and Meta-Analysis

Abstract: The aim of the current study was to evaluate the influence of severe radiation-induced lymphopenia (RIL) on the outcomes of esophageal cancer (EC). A systematic review and meta-analysis was performed through the PRISMA guideline. Seventeen studies were included in the current systematic review, with eight included in the meta-analyses. Meta-analyses found that severe RIL was associated with lower pathologic complete response (pCR) rate (odds ratio (OR) = 0.44, 95% confidence interval (CI) = 0.30–0.66, I2 = 0%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Recently, a study that included 110 ESCC receiving IMRT showed that radiation‐induced lymphopenia (RIL) was associated with cardiac and pulmonary dose parameters, and the results also demonstrated that RIL could predict survival and radiation pneumonia 29 . A meta‐analysis also revealed that RIL was associated with dosimetric factors such as PTV, cardiac dose, and effective dose to immune cells (EDIC), and it was correlated with lower pCR rates, as well as poorer OS and progression‐free survival (PFS) 30 . However, none of them analyzed the pericardial dose.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study that included 110 ESCC receiving IMRT showed that radiation‐induced lymphopenia (RIL) was associated with cardiac and pulmonary dose parameters, and the results also demonstrated that RIL could predict survival and radiation pneumonia 29 . A meta‐analysis also revealed that RIL was associated with dosimetric factors such as PTV, cardiac dose, and effective dose to immune cells (EDIC), and it was correlated with lower pCR rates, as well as poorer OS and progression‐free survival (PFS) 30 . However, none of them analyzed the pericardial dose.…”
Section: Discussionmentioning
confidence: 99%
“…The development of severe lymphopenia after radiation without concurrent chemotherapy or steroids use has been reported in patients with brain, head and neck, breast, pancreatic, esophageal, cervical, uterine, and lung cancer ( 52 , 78 ). Notably, according to systematic reviews and meta-analyses, post-radiation lymphopenia is associated with shorter survival in pancreatic and lung cancer ( 79 81 ), head and neck and esophageal cancer ( 79 , 82 84 ), urological cancer ( 85 ), nasopharyngeal and cervical cancer ( 47 ) and many other solid tumors ( 69 , 78 , 79 , 86 88 ). In agreement, a meta-analysis including 16 cancer types supports that radiation-induced lymphopenia is a significant prognostic factor for mortality in virtually all solid cancers ( 79 ).…”
Section: Standard Therapy-related Immunosuppression In Glioblastomamentioning
confidence: 99%
“…The implications of identifying some predictors of radiationinduced lymphopenia (RIL) are highlighted by the studies that analyze the correlations between the parameters of the multimodal treatment including radiation dosimetry and the decrease in absolute lymphocyte count. (Table 2) [71][72][73][74][75][76]. Esophagus Larger planning target volume (PTV), higher heart and body dose, higher EDIC Lymphocyte nadir after 4-6 weeks of radiotherapy [73] Brain (glioma), lung, pancreas Field size, dose per fraction, and fraction number SBRT, Proton therapy Increased risk of RIL [74] Reduction of RIL risk [74] Spleen Volumes receiving at least 5 Gy (V15) and maximum dose (Dmax) an increase of 1 Gy in mean splenic dose Nadir lymphocyte count [75] 1% decrease in absolute lymphocyte count at nadir [75] Esophagus EDIC < 2, 2 to 4, and >4 Gy, respectively 2-year OS rates were 66.7%, 42.7%, and 16.7% [76]…”
Section: Radiotherapy and Immunotherapy-from Research To Clinical Pra...mentioning
confidence: 99%